2023
DOI: 10.1039/d3mh00391d
|View full text |Cite
|
Sign up to set email alerts
|

Selective spectral absorption of nanofibers for color-preserving daytime radiative cooling

Abstract: Passive radiative cooling is a promising solution for cooling objects without consuming energy. However, chemical colors absorb visible light and generate heat, posing a challenge for designing a colored sub-ambient...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Firstly, it was demonstrated that nano- and micro-structures with a size comparable to the wavelength of the solar spectrum could serve as effective scatters to enable high solar reflection. 35,42,43 Meanwhile, due to its high refractive index, ZrO 2 may further enhance the solar scattering. These two factors endowed the PVDF composite film with high solar reflectivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, it was demonstrated that nano- and micro-structures with a size comparable to the wavelength of the solar spectrum could serve as effective scatters to enable high solar reflection. 35,42,43 Meanwhile, due to its high refractive index, ZrO 2 may further enhance the solar scattering. These two factors endowed the PVDF composite film with high solar reflectivity.…”
Section: Resultsmentioning
confidence: 99%
“…30–33 It has been demonstrated that nanofibers with a diameter comparable to the wavelength of the solar spectrum can serve as effective scatters to enable strong solar reflection. 34–37 Thus, fibrous films obtained by the electrospinning process have attracted significant attention in the field of radiation refrigeration due to their advantages of easy regulation of the fiber structure, high air permeability and elevated flexibility. Zhang et al 5 reported the preparation of a PVDF/Al 2 O 3 hybrid film by electrospinning, which has a high average solar reflectance of 97%.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, both microchannels and microgrooves should have a substantial effect on reflecting UV-vis-NIR. 58 Moreover, Mie scattering theory also directed that the microstructure will not obstruct the emission of light 59 when its size is smaller than the wavelength of light. Because the sizes of the aforementioned microgrooves and directional microchannels are far smaller than the mid-infrared radiation wavelength ( i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The different-size nanofibers could achieve different scattering effects at different wavelengths of visible light, giving the structure different colors. 113…”
Section: Application Of Radiative Coolingmentioning
confidence: 99%